Projeto arquitetônico para um estúdio de produção audiovisual localizado em Belém/PA - BRABO, Fernanda Martins Cavalcante (2023)
Following the continuous technological advances and the city’s development, the local artistic and audiovisual productions also grow on a daily basis. The present thesis has as it’s byproduct the architectural project for a studio - to attend the growing demand and offer all of the technical and practical support that is needed, with the useful shipping conteiner’s modularity as it’s main diferencial. For the thesis’ writing, the bibliographical research on selected and mentioned authors was used to abide the process of architectural design, along with interviews and site visiting.